Copper Corrosion Protection by 4-Hydrocoumarin Derivatives: Insight from Density Functional Theory, Ab Initio, and Monte Carlo Simulation Studies - Saprizal Hadisaputra; Agus Abhi Purwoko; Saprini Hamdiani (Universitas Gadjah Mada, 2022)
The corrosion inhibition performance of 4-hydrocoumarin derivatives has been studied using weight loss, electrochemical impedance spectroscopy, potentiodynamic polarization, and electrochemical frequency modulation techniques. However, experimental studies have not explained why the methoxy (OCH3) group contributes more to the increase in corrosion inhibition than the methyl (CH3) and chlorine (Cl) functional groups. In this theoretical study, the electronic aspect of the target corrosion inhibitors will be studied in detail to help strengthen the explanation in the experimental research. Density functional theory, ab initio, and Monte Carlo simulations have been used to analyze the corrosion inhibition performance of 4 curcumin derivatives against copper. The quantum chemistry approach is carried out under gas and aqueous conditions in neutral and protonated inhibitors. The Monte Carlo simulation was used to observe the dynamics and the mechanism of inhibition of the target molecule on the copper surface. The quantum chemistry approach can mimic the geometrical parameters of molecular inhibitors. It can also explain electronically why the OCH3 functional group is superior to other substituents. The adsorption energy of the 4-hydroquinone derivative is linearly correlated with the reported experimental study. The level of corrosion inhibition efficiency is OCH3 > CH3 > H > Cl.